Pelatihan Pemanfaatan Tanaman Obat Keluarga untuk Optimalisasi Kesehatan Berbasis Tradisional - Restu Prihandini; Victor Palapessy; Derry Trisna Wahyuni; Nanda Azzahra (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2026)
This community service program aims to enhance the knowledge and skills of the community in Pulau Akar, Setokok Village, Batam City, in utilizing Family Medicinal Plants (TOGA) for optimizing health based on traditional methods. The program was carried out through training involving housewives, community leaders, and local health cadres. The methods used include an initial survey, practical training on types of medicinal plants, their benefits, processing methods, and the distribution of TOGA seedlings to be planted at participants' homes. Additionally, group discussions were held to reinforce understanding and organize TOGA utilization within the community. The results of this program showed a significant increase in participants' understanding and skills regarding the use of TOGA for treating minor ailments and disease prevention. The community began planting TOGA around their homes, creating herbal gardens that can be used as a source of natural medicine. Furthermore, the emergence of local leaders actively disseminating knowledge about TOGA was an important outcome of this service. Social change was also evident as the community became more aware of the importance of managing health independently using local resources. It is hoped that this program will continue with regular training and the strengthening of TOGA utilization groups to ensure the sustainability of this program in the future.